2018
DOI: 10.1093/scan/nsy022
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of left anterior intraparietal sulcus shows that mutual adjustment marks dyadic joint-actions in humans

Abstract: Creating real-life dynamic contexts to study interactive behaviors is a fundamental challenge for the social neuroscience of interpersonal relations. Real synchronic interpersonal motor interactions involve online, inter-individual mutual adaptation (the ability to adapt one’s movements to those of another in order to achieve a shared goal). In order to study the contribution of the left anterior Intra Parietal Sulcus (aIPS) (i.e. a region supporting motor functions) to mutual adaptation, here, we combined a b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
28
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 58 publications
6
28
0
Order By: Relevance
“…Nevertheless, the present results are suggestive that posterior parietal alpha suppression reflects the visual coupling governing movement coordination between partners, whether virtual or not. Our data also expands current knowledge on parietal dynamics during on-line social interaction (Tognoli et al, 2007;Era et al, 2018b) by highlighting an increase of source-resolved gamma power over right temporo-parietal areas during social coordination compared to solo actions ( Figure 4C). Finally, interactions marked with high levels of emotional responses elicited increased alpha in a similar right parietal-temporal-insular complex ( Fig.…”
Section: Coordination Of Self and Other Neural Network And The Role supporting
confidence: 80%
See 1 more Smart Citation
“…Nevertheless, the present results are suggestive that posterior parietal alpha suppression reflects the visual coupling governing movement coordination between partners, whether virtual or not. Our data also expands current knowledge on parietal dynamics during on-line social interaction (Tognoli et al, 2007;Era et al, 2018b) by highlighting an increase of source-resolved gamma power over right temporo-parietal areas during social coordination compared to solo actions ( Figure 4C). Finally, interactions marked with high levels of emotional responses elicited increased alpha in a similar right parietal-temporal-insular complex ( Fig.…”
Section: Coordination Of Self and Other Neural Network And The Role supporting
confidence: 80%
“…Despite their essential role, social interactions still remain the "dark matter" of social neuroscience: the field is in urgent need of studies that embrace the reciprocal and real-time nature of social coordination (Hari and Kujala, 2009;Dumas, 2011;Hasson et al, 2012;Konvalinka and Roepstorff, 2012;Schilbach et al, 2013;Hari et al, 2015). Overcoming the methodological challenge of bringing a true interactive context into the laboratory, some innovations have allowed behavioral tracking, brain recording and stimulation of multiple participants in interaction (Montague et al, 2002;Babiloni et al, 2006;Tognoli et al, 2007;Dumas et al, 2010;Funane et al, 2011;Moreau et al, 2016;Chen et al, 2017;Dikker et al, 2017;Hirsch et al, 2017;Novembre et al, 2017;Era et al, 2018b). Such investigations have exposed the neural underpinnings of our propensity to interact with others during sensorimotor coordination (Tognoli and Kelso, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Whilst previous work has quantitatively examined the kinematic elements of imitative behavior in both healthy people (e.g., Braadbaart et al, 2012;Campione & Gentilucci, 2011;Era et al, 2018;Forbes & Hamilton, 2017;Gold et al, 2008;Hayes et al, 2016;Krüger et al, 2014;Pan & Hamilton, 2015;Reader & Holmes, 2015;Reader et al, 2018;Sacheli et al, 2012;Sacheli et al, 2013, Sacheli, Christensen, et al, 2015Wild et al, 2010;Williams et al, 2013) and brain-damaged patients (e.g., Candidi et al, 2018;Hermsdörfer et al, 1996), as far as we are aware no previous experiments have looked at so many components of the velocity profile in order to compare the coarse-grained (i.e., wrist) kinematic approach to meaningful and meaningless action imitation. Much informative work has been done to assess action performance in meaningful and meaningless action imitation (e.g., Buxbaum et al, 2014;Goldenberg & Hagmann, 1997;Mengotti et al, 2013), but frequently using only subjective rating measures.…”
Section: Kinematics In Meaningful and Meaningless Action Imitationmentioning
confidence: 99%
“…We used an ecological and controlled human-avatar interactive task (Sacheli et al, 2015a;2015b;Candidi et al, 2017;Era et al, 2018a;Gandolfo et al, 2019), which has been shown to recruit the same behavioural processes called into play during human-human interaction, namely mutual adjustment and automatic imitation 2013;Candidi et al, 2015;Curioni et al, 2017;Era et al, 2018b). Importantly, in the present task, one's own action goal cannot be achieved without considering the virtual partner's online movements and adapting to them.…”
Section: Experimental Taskmentioning
confidence: 99%